Individual differences in face and voice matching abilities: The relationship between accuracy and consistency. Issue 1 (26th October 2020) - Kramer, Robin S. S.; Jones, Alex L.; Gous, Georgina
Summary: Deciding whether two different face photographs or voice samples are from the same person represent fundamental challenges within applied settings. To date, most research has focussed on average performance in these tests, failing to consider individual differences and within‐person consistency in responses. Here, participants completed the same face (Experiment 1) or voice matching test (Experiment 2) on two separate occasions, allowing comparison of overall accuracy across the two timepoints as well as consistency in trial‐level responses. In both experiments, participants were highly consistent in their performances. In addition, we demonstrated a large association between consistency and accuracy, with the most accurate participants also tending to be the most consistent. This is an important result for applied settings in which organisational groups of super‐matchers are deployed in real‐world contexts. Being able to reliably identify these high performers based upon only a single test informs regarding recruitment for law enforcement agencies worldwide.